2010
DOI: 10.1089/vbz.2009.0196
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Flaviviruses and Orthobunyaviruses in Mosquitoes in the Yucatan Peninsula of Mexico in 2008

Abstract: A total of 191,244 mosquitoes from 24 species were collected in the Yucatan Peninsula of Mexico from January to December 2008, and tested for the presence of cytopathic virus by virus isolation in Vero cells. Eighteen virus isolates were obtained, all of which were orthobunyaviruses. These were identified by reverse transcriptionpolymerase chain reaction (RT-PCR) and nucleotide sequencing as Cache Valley virus (n ¼ 17) and South River virus (n ¼ 1). A subset (n ¼ 20,124) of Culex quinquefasciatus collected thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 33 publications
0
60
0
2
Order By: Relevance
“…44 All other viruses were isolated during our previous entomologic investigations in the Yucatan Peninsula and have been described elsewhere. [4][5][6] The PRNTs were performed using African green monkey kidney (Vero) cells. Initially, all serum samples were screened at a single dilution of 1:20.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…44 All other viruses were isolated during our previous entomologic investigations in the Yucatan Peninsula and have been described elsewhere. [4][5][6] The PRNTs were performed using African green monkey kidney (Vero) cells. Initially, all serum samples were screened at a single dilution of 1:20.…”
Section: Methodsmentioning
confidence: 99%
“…This poorly characterized virus was originally isolated from mosquitoes in New Jersey in 1960 40 and later from mosquitoes in Pennsylvania, 41 Georgia (Mead DG, unpublished data) and the Yucatan Peninsula. 6 The SOURV isolate from Mexico is genetically and serologically distinct from the prototype strain and represents a novel subtype of SOURV. 42 Until now, there have been no published studies that reported detection of antibodies to SORV in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…sollicitans and Oc. taeniorhynchus in coastal regions of the mid-Atlantic and Gulf Coast United States and central America (Calisher et al 1986 and references therein, Farfan-Ale et al 2010), and Oc. trivittatus in New York State (Ngo et al 2006).…”
mentioning
confidence: 99%